2008
DOI: 10.1359/jbmr.070813
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Obesity and Osteoporosis: Effect of Fat Mass on the Determination of Osteoporosis

Abstract: It was previously believed that obesity and osteoporosis were two unrelated diseases, but recent studies have shown that both diseases share several common genetic and environmental factors. Body fat mass, a component of body weight, is one of the most important indices of obesity, and a substantial body of evidence indicates that fat mass may have beneficial effects on bone. Contrasting studies, however, suggest that excessive fat mass may not protect against osteoporosis or osteoporotic fracture. Differences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

21
328
6
18

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 450 publications
(395 citation statements)
references
References 207 publications
(285 reference statements)
21
328
6
18
Order By: Relevance
“…Other recent reviews have discussed the mechanisms that might link obesity and adiposity to bone and fracture risk. (1)(2)(3)(4)(5)(6) Large Proportion of Elderly That Are Overweight or Obese, Compared to Underweight seven studies that evaluated BMI as a risk factor for fracture demonstrated a nonlinear pattern in the relationship between fracture risk and BMI. (11) There was a marked increase in fracture risk from normal to low BMI (<25 kg/m 2 ), and the reduction in risk was particularly large for hip fracture (approximately onequarter the risk of those with normal BMI).…”
Section: Introductionmentioning
confidence: 99%
“…Other recent reviews have discussed the mechanisms that might link obesity and adiposity to bone and fracture risk. (1)(2)(3)(4)(5)(6) Large Proportion of Elderly That Are Overweight or Obese, Compared to Underweight seven studies that evaluated BMI as a risk factor for fracture demonstrated a nonlinear pattern in the relationship between fracture risk and BMI. (11) There was a marked increase in fracture risk from normal to low BMI (<25 kg/m 2 ), and the reduction in risk was particularly large for hip fracture (approximately onequarter the risk of those with normal BMI).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that obesity and osteoporosis share several common genetic and environmental factors [2]. Body fat mass, a component of body weight, is an important measure of obesity, and a considerable evidence indicates that fat mass may have beneficial effects on bone [2].…”
Section: Introductionmentioning
confidence: 99%
“…(20) There are strong reasons to expect a pathophysiologic linkage between fat and bone tissue. Osteoblasts and adipocytes in bone marrow originate from the same mesenchymal stem cells, (21) normal aging is associated with a high incidence of both osteoporosis and bone marrow adiposity, (22,23) and both bone remodeling and adiposity are regulated by the hypothalamus and sympathetic nervous system. (22) Fat and bone are also linked biomechanically.…”
mentioning
confidence: 99%
“…Osteoblasts and adipocytes in bone marrow originate from the same mesenchymal stem cells, (21) normal aging is associated with a high incidence of both osteoporosis and bone marrow adiposity, (22,23) and both bone remodeling and adiposity are regulated by the hypothalamus and sympathetic nervous system. (22) Fat and bone are also linked biomechanically. Bone adapts to the mechanical loads imposed on it, and these loads ultimately arise from supporting or moving body or limb mass against gravity and inertial forces.…”
mentioning
confidence: 99%